Phenol Oxidative Dearomatization of Modified Nucleoside Templates: A Simple Access to the C7-Spiroannulated Octosyl Acid Framework - Mullapudi, Venkannababu; Bhogade, Ravindra B.; Deshpande, Mukund V.; Ramana, Chepuri V. (Synthesis, 2017)
Phenol oxidative dearomatization and cyclization has been executed successfully on nucleoside templates to synthesize C7-spiroannulated perhydrofuropyran nucleosides and C6-spiroannulated perhydrofurofuran nucleosides as novel analogues of octosyl acid and related peptidyl nucleosides.
Keywords: phenol oxidative dearomatization; peptidyl glycosides; modified nucleosides; Vorbrüggen glycosylation; glucose diacetonide